2007
DOI: 10.1111/j.1365-2885.2007.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftriaxone after intravenous, intramuscular and subcutaneous administration to domestic cats

Abstract: The pharmacokinetic properties of ceftriaxone, a third-generation cephalosporin, were investigated in five cats after single intravenous, intramuscular and subcutaneous administration at a dosage of 25 mg/kg. Ceftriaxone MICs for some gram-negative and positive strains isolated from clinical cases were determined. Efficacy predictor (t > MIC) was calculated. Serum ceftriaxone disposition was best fitted by a bicompartmental and a monocompartmental open models with first-order elimination after intravenous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This is confirmed by comparing the clearance for ceftazidime in cats (0.190 L/kg/h) to the glomerular filtration rate (GFR) measured in cats (renal inulin clearance) of 0.182 L/kg/h) [17]. For ceftriaxone it is reported that the mechanism of excretion in cats is through glomerular filtration and tubular secretion and/or non-renal excretion with a clearance of 0.370 L/kg/h [18], which exceeds the GFR in cats. In dogs the measured GFR (renal inulin clearance) is 0.235 L/kg/h [17].…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed by comparing the clearance for ceftazidime in cats (0.190 L/kg/h) to the glomerular filtration rate (GFR) measured in cats (renal inulin clearance) of 0.182 L/kg/h) [17]. For ceftriaxone it is reported that the mechanism of excretion in cats is through glomerular filtration and tubular secretion and/or non-renal excretion with a clearance of 0.370 L/kg/h [18], which exceeds the GFR in cats. In dogs the measured GFR (renal inulin clearance) is 0.235 L/kg/h [17].…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous study, the minimum inhibitory concentration (MIC) of ceftriaxone is usually less than 2 μg/mL. [1][2][3] Here, the ceftriaxone disodium salt level in discs (4.0 ± 1.7 μg/mL) was higher than MIC, and within the therapeutic level. Because ceftriaxone could penetrate into the intervertebral disc, and the level of ceftriaxone reached MIC, postoperative discitis could be prevented and the preoperative prophylaxis is meaningful.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] There is a high prevalence of postoperative infection in the intervertebral disc space, and the orthopaedist will usually use antibiotics to prevent disc infections. Prophylaxis is a way to decrease the incidence of postoperative discitis, which is an infection in intervertebral disc space.…”
Section: -3mentioning
confidence: 99%
“…But, reabsorption may also occur in intestine. Although the previous studies on intramuscular pharmacokinetics of ceftriaxone in cow calves (Soback et al,1988;Johal &Srivastava, 1998), camel (Goudah, 2008), cat (Abarellos et al, 2007) and goat ( Ismail et al, 2005) did not reveal any absorptionreabsorption pattern but probably blood collection at frequent interval of time may show the two phases. The veterinarians frequently use ceftriaxone intramuscularly for treatment of susceptible bacterial infections.…”
Section: Introductionmentioning
confidence: 81%